Mastering story, community and influence : how to use social media to become a socialeader - Oatway, Jay (Wiley, 2012)
"How to craft social media messaging that will engage your audience and make you a leader in your field From celebrated social media authority Jay Oatway, Tell It Well takes a different approach to social media by focusing on the message rather than the media itself. The book shows you how to use your innate ability to share stories and turn it into a powerful and influential skill in the social media universe. You'll build the kind of online relationships and influence that will boost your impact, influence, and career. You'll not only establish online influence for your business and yourself, but also learn to future-proof you own career. Based on timeless storytelling fundamentals rather than current social media fads, Tell It Well shows you how to develop narratives that will build social currency for success today and tomorrow"--